Changes Detection Of Land Surface Temperature Over Southern Of Iraq During Period (1990 – 2022) Using Landsat Data: Changes Detection Of Land Surface Temperature Over Southern Of Iraq - Tawfik, Marwa (ASJ - Academic Science Journal, 2025)
Land surface temperature (LST) is a crucial climate variable for climate change studies. It provides valuable data for understanding land surface conditions and land-atmosphere interactions. This study examines the spatial and temporal patterns of LST in Basra, Thi-Qar, and Maysan, three provinces in southern Iraq. Using Landsat 5 and 8 imagery from 1990, 2013, and 2022, we estimated LST for July (summer) and December (winter) of each year, employing ArcGIS 10.8. Supervised classification was used to categorize the spectral pixels of the LST into different ranges. The results show an increase in temperatures in July across the study area, notably in Basra and Zubair districts in Basra Governorate, most areas of Thi-Qar like Shatra, and parts of Maysan, which is considered humid due to existing marshes. In July, LST ranged from 23-58°C in Basra, 21-55°C in Thi-Qar, and 23-57°C in Maysan. In December, the LST ranged from 3-24°C in Basra, 3-28°C in Thi-Qar, and 4-23°C in Maysan. The findings indicate that LST values are mainly influenced by changes in land surface cover. From 1990 to 2022, there was a significant increase in LST across all cities, especially within the thermal range of 41-51°C in summer. Similarly, in December, there was a continuous increase in LST areas within the range of 16-22°C, with more pronounced increases observed in Basra and Maysan in 2022.